The geodiversity of the Abruzzo, Lazio, and Molise National Park (Central Italy) - Gianluca Esposito; Vania Mancinelli; Giorgio Paglia; Francesco Ciavattella; Daniela D’Amico; Cinzia Sulli; Luciano Sammarone; Enrico Miccadei (Journal of Maps, 2023)
ABSTRACTThis paper presents a novel geodiversity map of the Abruzzo, Lazio, and Molise National Park (Central Italy). The Park exhibits a wide range of geological-geomorphological environments of great scientiﬁc and touristic interest, offering unique landscapes and wild nature frequented by visitors year-around. All these features reflect a marked geodiversity and a valuable geoheritage, requiring protection and valorization activities. The geodiversity map that we present was realized following an integrated methodological approach, which includes and combines geological-geomorphological features, geoheritage elements, data from Park archives, and new field-based observations. In this framework, the map serves as a key outreach tool for the dissemination of the geological information of the area and for the promotion of its geodiversity through a modern, sustainable, and environmentally aware tourism in an highly frequented protected area.